A conserved retina-specific gene encodes a basic motif/leucine zipper domain. - Swaroop, A (1992)
Using subtraction cloning, we have isolated a human cDNA, AS321, which is expressed in retina and retinoblastoma cell lines but not in any other tissue or cell line tested. AS321 mRNA is detected in all cells of neural retina, with a high level of expression in photoreceptors. The polypeptide sequence deduced from the cDNA reveals consensus phosphorylation sites for protein kinase A and proline-directed protein kinase. Its C-terminal region contains a basic motif and a leucine zipper domain similar to the DNA binding proteins of the jun and fos oncoprotein family, and it shows a strong similarity to the product of an avian retroviral oncogene, v-maf. The gene for AS321 is conserved during evolution and is expressed in vertebrate retina. We propose to name the gene NRL (neural retina leucine zipper.